CD39+ REGULATORY T CELLS IN PULMONARY SARCOIDOSIS AND LOFGREN'S SYNDROME - Igor Vladimirovich Kudryavtsev; Natalia Mihailovna Lazareva; Olga Petrovna Baranova; Alexey Sergeevich Golovkin; Dmitry Valer’evich Isakov; Maria Konstantinovna Serebriakova; Tatyana Pavlovna Ses’; Mikhail Mikhailovich Ilkovich; Areg Artemovich Totolian (Медицинская иммунология, 2019)
Sarcoidosis is a disorder of unknown etiology characterized by development of necrosis-free epithelioid cell granulomas in various tissues. There are two main phenotypes of pulmonary sarcoidosis (PS): Lofgren's syndrome (LS) is an acute form with favorable outcome, while non-Lofgren's syndrome (nLS) is a chronic type of disease that can lead to pulmonary fibrosis in 20 % of cases. Our study was aimed at investigating changes in the main cell-surface differentiation antigens on peripheral blood regulatory T cells (Tregs) from patients with first diagnosed PS without treatment (LS (n=11) and nLS (n=46)) compared to healthy volunteers (HC, n=26), that might be used as immunological markers for predicting severity of this disorder. Flow cytometry analysis of peripheral blood cell samples demonstrated that patients with nLS had decreased relative number of CD3+ cells vs. HC as well as CD3+CD4+ cells vs. HC and LS patients. Furthermore, the relative and absolute number of Tregs were also decreased in nLS group vs. HC (2.83% (2.47; 3.36) vs. 3.33% (2.79; 3.84), p=0.021) and 37 (29; 52) cells vs. 50 (42; 65), p=0.004, respectively) per one microliter peripheral blood. A relative number of CD39-positive Тregs in chronic vs. acute sarcoidosis patients was associated with 51.02% (38.20; 61.62) vs. 48.64% (41.46; 63.72) that was significantly (p<0.001 and p=0.007, respectively) higher than in HC (39.52% (11.55; 46.34). It was found that “naïve” (CD45R0–CD62L+) Тregs did not significantly differ in percentage of CD39- and CD73-positive cells in all groups tested. Moreover, CD45R0+CD62L+ Тregs in LS and nLS patients contained significantly more CD39-positive cells (69.66% (61.92; 79.34) and 67.62% (61.92; 79.34), respectively, compared to 47.55% (15.74; 65.32) in HC (p<0.001 and p=0.004, respectively). In case of CD45R0+CD62L– Tregs able to exit from the circulation and migrate to the site of inflammation, an increased percentage of CD39-positive subset was noted only in patients with chronic sarcoidosis and HC (61.79% (55.12; 73.09) and 57.27% (16.03; 66.98), p=0.006). Enhanced CD39 expression on Tregs seems to be related to chronic immune response, so that antigen elimination becomes impossible due to Treg overactivation, as shown in patients with sarcoidosis and in some other chronic autoimmune and infectious disorders.